NPC1 regulates ER contacts with endocytic organelles to mediate cholesterol egress - Höglinger, Doris; Burgoyne, T.; Sanchez-Heras, E.; Colaco, A.; Newton, J.; Hempelmann, Pia; Platt, Farina Marie; Eden, Emily R. (Nature Communications, 2019)
Though endocytosed dietary cholesterol is transferred to the endoplasmic reticulum (ER), how this is regulated is unclear. Here, the authors report a role for Niemann-Pick Type C Protein 1 (NPC1) in tethering endocytic organelles to the ER, which may contribute to interorganelle cholesterol transport.
Gesehen am 21.10.2019